Behavior, blood stress indicators, skin lesions, and meat quality in pigs transported to slaughter at different loading densities - Urrea, Valentina Montoya [UNESP]; Bridi, Ana Maria; Ceballos, Maria Camila; Paranhos da Costa, Mateus J R [UNESP]; Faucitano, Luigi [UNESP] (Oxford University Press (OUP), 2021)
A total of 1,936 pigs were transported through 8 trips (8.4 ± 0.5 hr) from 2 grow-to-finish farms to a commercial slaughter plant, all located in Southern Brazil. On each trip, a sub-sample of each load (36 barrows/load, weighing 118.9 ± 9.8 kg) was randomly allocated into one of the following loading densities during transport: 200 kg/m2 (D200), 235 kg/m2 (D235), and 270 kg/m2 (D270). Behavioral recordings of postures and activities were made during transportation and lairage using video-cameras. At slaughter, blood samples were collected to assess the concentrations of creatine kinase (CK) and lactate. Carcass weights and skin lesion scores were assessed on-line, and meat quality was evaluated in the longissimus thoracis (LT) muscle by assessing pH, color, and drip loss. During transportation, the proportion of animals lying down was higher (P < 0.05) in D200 and D235 groups compared with D270. The proportion of sitting animals during transportation was higher (P < 0.01) in D270 compared with D200. In lairage, D200 and D235 pigs stood more compared with D270 (P = 0.01), while the proportion of lying pigs was higher (P = 0.02) for D270 pigs compared with D200 and D235. The frequency of drinking bouts in lairage was higher (P < 0.05) for D200 group compared with D235 and D270. The levels of CK were lower (P < 0.05) in D200 pigs transported compared with D270. Lesion scores tended to be higher (P = 0.06) in D270 carcasses compared with D200 and D235. A tendency for lower (P = 0.10) pH1 values in the LT muscle of D270 pigs compared with D200 pigs was also found. Based on the results of this study, the application of lower loading densities (≤235 kg/m2) in the truck allows pigs to have sufficient space to rest, travel more comfortably and arrive less fatigued at the slaughter plant.
Keywords: animal welfare; behavior; loading density; meat quality; pigs; transport